INTERAKSI STRUKTUR PONDASI DENGAN KOLOM PADA PROYEK PEMBANGUNAN RSUD MAJALENGKA - Ramadhan, Gilang; kholiq, Abdul (Universitas Majalengka, 2019)
Project to build an outpatient and basement building in Majelngka District Hospital consists of 4 floors and one basement floor. The foundation used in this project is a deep foundation with borepie type foundation. Each foundation must be able to withstand the load generated by the interaction of building structures. the foundation with this column can later be used as a comparison with the existing foundation and column design. Soil type in this project is clay type with hard soil depth of more than 10 m. The calculation of foundation and column is assisted with the SAP 2000 software. Based on the calculation results obtained the dimensions of the foundation with a diameter of 0.5 m with a depth of 5 m using the main level 8D19 with stirrup layer D10-200 and pilecap thickness used for 0.6 m while the structural data from implementing contractor obtained the dimensions of the foundation with a diameter of 0.8 m with a pole length of 4 m, the main reinforcement 16D19 with stirrup D10-150 and pilecap thickness obtained 1 m. This difference occurs because of differences in the calculation concepts of each method.